Self-inflicted wound with a nail in the heart: case report - Reyna Sepúlveda, Francisco J.; Cueto Ramos, Rubén Gerardo; Vásquez Fernández, Francisco; Hernández Guedea, Marco Antonio; Guevara Charles, Asdrúbal; Muñoz Maldonado, Gerardo Enrique (UANL. Facultad de Medicina, 2016)
Adequate diagnosis and treatment of penetrating cardiac injury (PCI) represents a great challenge for the surgeon in the emergency department (ED) because of its high mortality. It is estimated that more than 90% of mortality happens before the patient reaches the hospital and only 15---50% of those will receive appropriate medical treatment. Case report: A 42-year-old hemodynamically stable male is brought to the ED with a protruding nail in his thorax. He is taken to the operating room (OR) where a medial sternotomy is performed and an injury is found in the left ventricle. Cardiac muscle repair is performed with pericardial patch. Discussion: PCI from a suicide attempt secondary to a nail hammered into the chest is very rare and no previous reports were found by the author. Conclusion: The objects that penetrate cardiac structures must be removed in a proper OR with capable personnel and the resources available to perform procedures like an urgent thoracotomy or sternotomy.